G Cubed Model Analysis: The Impact of Loss of Confidence In Emerging Countries on The World Economy - Ardi Sugiyarto (Media Ekonomi dan Manajemen, 2019)
Financial liberalization has significant role in fostering economic growth in the developing countries. However, it also cause a risk for the emerging countries when the advanced countries make an interest rate adjustment. This paper try to examine the economic adjustment both on emerging countries and advanced countries in response to the shift of risk perception in emerging countries. This study will simulate the shock of risk perception in emerging countries by using intertemporal general equilibrium economic model that are called G-Cubed Model. The simulation result from the model indicates that international financial flow has a significant role in explaining the spill over effect of the lost confidence in emerging countries. In the short run, there is a significant drop in consumption and private investment in emerging countries. In the long run output of the emerging countries is expected steady below the baseline. On the other hand, in advanced countries, there is a significant increase in private consumption and investment in the short run. Moreover, it is expected that lower interest rate stimulates the investment in the future in advanced countries.Keywords: G-Cubed, emerging, simulation, risk, financial flowLiberalisasi keuangan memiliki peran penting dalam mendorong pertumbuhan ekonomi di negara-negara berkembang. Namun, liberalisasi keuangan juga akan menimbulkan risiko bagi negara-negara berkembang ketika negara-negara maju melakukan penyesuaian suku bunga. Penelitian ini bertujuan untuk melakukan analisis dampak dari pergeseran persepsi risiko baik bagi negara-negara berkembang maupun negara-negara maju. Studi ini akan mensimulasikan pergeseran persepsi risiko di negara-negara berkembang dengan menggunakan model ekonomi keseimbangan umum antarwaktu yang disebut Model G-Cubed. Hasil simulasi dari model menunjukkan bahwa aliran keuangan internasional memiliki peran yang signifikan dalam menjelaskan efek tumpahan dari hilangnya kepercayaan di negara-negara berkembang. Dalam jangka pendek, ada penurunan konsumsi dan investasi swasta yang signifikan di negara-negara berkembang. Dalam jangka panjang, output dari negara-negara berkembang diperkirakan stabil di bawah baseline. Di sisi lain, di negara maju, ada peningkatan konsumsi dan investasi swasta yang signifikan dalam jangka pendek. Selain itu, diharapkan suku bunga yang lebih rendah merangsang investasi di masa depan di negara-negara maju.Kata Kunci: G-Cubed, negara emerging, simulasi, risiko, arus keuangan